2016
DOI: 10.1007/s10570-016-1080-1
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation behavior of aqueous cellulose nanocrystals: the effect of inorganic salts

Abstract: Natural anisotropic building-blocks such as cellulose nanocrystals (CNCs) have attracted considerable attention due to their biodegradability and nanometer-size. In this work the colloidal behavior of CNCs, obtained from sulfuric acid hydrolysis of microcrystalline cellulose, has been studied in presence of salts of different valences. The influence on the colloidal stability and nature of aggregates has been investigated for monovalent salts (LiCl, NaCl, KCl, CsCl), divalent salts (CaCl 2 and MgCl 2 ), and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
113
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(125 citation statements)
references
References 44 publications
(43 reference statements)
10
113
0
Order By: Relevance
“…Most studies involved the effect of small electrolyte concentrations on ζ potential, particle size, pitch length, alignment and phase formation in aqueous CNC suspensions. 33 , 36 38 Alkaline condition used in preparing CNC/lignin films in this study showed the effect of NaOH on the film transparency. This, to the authors knowledge, is the first attempt to show the effect of NaOH addition on the CNC film transparency.…”
Section: Resultsmentioning
confidence: 83%
“…Most studies involved the effect of small electrolyte concentrations on ζ potential, particle size, pitch length, alignment and phase formation in aqueous CNC suspensions. 33 , 36 38 Alkaline condition used in preparing CNC/lignin films in this study showed the effect of NaOH on the film transparency. This, to the authors knowledge, is the first attempt to show the effect of NaOH addition on the CNC film transparency.…”
Section: Resultsmentioning
confidence: 83%
“…The precipitation-redispersion mechanism enabled the removal of more than 99.8% of the ionic residues. Consequently, the nanoparticle dispersions showed no macroscopic phase separation over several weeks at 23 • C. Nevertheless, the presence of ions in the dispersions is expected to promote the formation of agglomerates [55,56] effecting larger apparent particle sizes. The actual particle size could be detected by atomic force microscopy and transmission electron microscopy.…”
Section: Nanoparticle Dispersionsmentioning
confidence: 98%
“…At the lower limit, the electrostatic repulsions are dominant and very long‐range, promoting kinetic arrest, even at low CNC concentration (≈1 wt%); this is generally referred to as a repulsive Wigner glass, but for sufficiently long aspect ratios (e.g., bacterially derived CNC) it can slowly evolve into a nematic phase (e.g., after a week, for I < 10 µM) . At the upper limit, which strongly depends on the counter‐ion valence, the colloidal stability is disrupted and leads to either a slow evolution into an attractive colloidal gel, or to flocculation and sedimentation . Notably, the use of insufficiently charged CNCs results in similar behavior …”
Section: Self‐assembly From Suspension To the Solid Statementioning
confidence: 99%